THE PROCESS OF SETTING THE TIME FOR A1-B2 RFL EXAMS - ARIEȘAN, Antonela (Studia Universitatis Babeș-Bolyai Philologia, 2017)
The process of setting the time for A1-B2 RFL exams. In this paper we approach the issue of setting the time for each of the four RFL exams (A1-B2), administered by the Department of Romanian Language, Culture and Civilisation, from Babeș-Bolyai University, as part of the academic programme specific to the preparatory year, by presenting the stages this process was put through. In order to establish the total time interval for each exam, it was necessary to find a way to determine how much time is needed for each of the test’s components. Therefore, starting with an estimated timeframe decided beforehand in the specifications document, we have tried to confirm it or adjust it with the help of the pretesting and the actual examinations. During this process, attention was paid to the three parts of the written exam, Reading, Elements of the communication construction and Writing, excluding from the analysis the Listening and the Speaking component, which already had a set time for each test. We have doubled our analysis with the help of a qualitative method, the analysis of the feedback questionnaires, and the results obtained can be found in the last section of our paper. Rezumat. Procesul de stabilire a timpilor pentru examenele RLS, A1-B2. În acest studiu abordăm problema stabilirii timpului alocat pentru fiecare dintre cele patru examene de limba română ca limbă străină (RLS), A1-B2, administrate la Departamentul de limbă, cultură și civilizație românească, de la Universitatea Babeș-Bolyai, pe parcursul programului academic intitulat Anul pregătitor de limba română. Pentru a putea stabili cu exactitate timpul total pentru fiecare examen, o metodă de măsurare și înregistrare a timpilor pentru fiecare component al testului în parte a fost necesară. Așadar, s-a început cu un interval de timp stabilit anterior în documentele de specificații pentru examene, care a fost, după caz, confirmat, infirmat sau ajustat, în funcție de rezultatele obținute la pretestări și la examene. Pe parcursul acestui proces, o atenție sporită s-a acordat componentelor: Citire, Elemente de construcția comunicării și Scriere, excluzând din analiză Ascultarea și Vorbirea, pentru care există timpi ficși. În demersul nostru, am încercat să dublăm analiza cantitativă printr-o analiză calitativă, efectuată cu ajutorul chestionarelor de feedback, administrate la finalul examenului. Cuvinte-cheie: stabilirea timpilor, component, pretestare, examen, candidați.